Natural regeneration in semideciduous ombrophilous forest fragment in Sergipe state, Brazil - Fernandes, Milton Marques; Silva, Thalita Rocha; Pinto, Alexandre Siqueira; Souza, Icaro Bruno Andrade; Fernandes, Márcia Rodrigues de Moura (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
The objective of this study was to evaluate floristic, phytosociology and floristic similarity between the regenerative stratum of two areas of a semideciduous ombrophilous forest fragment, in different successional stages (initial and advanced), in Sergipe state. For the evaluation of the natural regeneration of the tree species, 10 plots of 10 m2 (2 m x 5 m) were systematically allocated in each area. All regenerating individuals were inventoried at an inclusion level of less than or equal to 15 cm. The parameters of the horizontal structure, Shannon diversity, Pielou equability and floristic similarity between the studied areas were calculated. The advanced successional forest presented more species, of climax ecological group, however the species with greater number of individuals are pioneers in the two areas. The lower incidence of light in the natural regeneration of the advanced successional forest resulted in a higher density of regeneration species. Both areas had floristic and diversity similarity.